Ushul Fiqh sebagai Alat Mitigasi Penyebaran Paham Radikalisme di Kampus - Rosadi, Khumaini (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This article discusses the role of Usul Fiqh as an epistemological instrument in mitigating the spread of radicalism in the campus environment. Usul Fiqh, as a methodology for understanding religious texts systematically, logically, and contextually, has great potential in fortifying students from textualist and extreme religious understandings. Amid the increasing symptoms of religion-based radicalism among young intellectuals, understanding the principles of Usul Fiqh such as maqāṣid al-syarī‘ah, sadd al-dzarī‘ah, and istihsān is crucial for instilling a moderate, inclusive, and rational way of thinking. This article uses a qualitative approach with literature study and normative analysis to describe how the integration of Usul Fiqh in the curriculum and academic activities can strengthen students' resilience against radical ideology. The article's findings indicate that strengthening the understanding of Usul Fiqh not only improves critical religious literacy but also serves as an effective ideological tool in fostering tolerance, peace, and coexistence amidst campus diversity. Thus, Usul Fiqh plays a strategic role as an academic and theological bulwark against the threat of religious radicalism.